Description of Environmental Care Analysis of Students in Elementary Schools - Medina, Joneil B (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aims to describe the environmental care character of students at the elementary school level.Methodology: This research is qualitative research with a systematic literature review type. The data in this study is secondary data in the form of research results documents related to this research. The population in this study was obtained from the Google Scholar site with the selected article criteria related to the search keywords. The total population obtained is 25 articles from Google Scholar.Main Findings: The main findings explain the essential factors in instilling the Caring for the Environment character in elementary school students. By caring for the environment, students can recognize the types of waste according to their group. The impact caused by students, besides making students comfortable learning, also helps students get used to living healthy and clean.Novelty/Originality of this study: This research seeks to describe the character of caring for the environment through literature studies from previous studies on caring for the environment in elementary schools.